2003
DOI: 10.1117/12.476242
|View full text |Cite
|
Sign up to set email alerts
|

Supervised multimedia categorization

Abstract: Static multimedia on the Web can already be hardly structured manually. Although unavoidable and necessary, manual annotation of dynamic multimedia becomes even less feasible when multimedia quickly changes in complexity, i.e. in volume, modality, and usage context. The latter context could be set by learning or other purposes of the multimedia material. This multimedia dynamics calls for categorisation systems that index, query and retrieve multimedia objects on the fly in a similar way as a human expert woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This classification mapping produced effective indexes used by search engines and retrieval systems over bibliographical archives or digital databases. Among the research results in this area, Frank Aldershoff et al [1] showed that categories help the users to navigate inside the digital data collections. By grouping the data via comprehensible categories, the users can quickly eliminate the non-relevant or non-interesting data.…”
Section: Multi-faceted Resource Categorizationmentioning
confidence: 99%
“…This classification mapping produced effective indexes used by search engines and retrieval systems over bibliographical archives or digital databases. Among the research results in this area, Frank Aldershoff et al [1] showed that categories help the users to navigate inside the digital data collections. By grouping the data via comprehensible categories, the users can quickly eliminate the non-relevant or non-interesting data.…”
Section: Multi-faceted Resource Categorizationmentioning
confidence: 99%
“…The multifaceted metadata has been created by mapping the attributes in the AAT hierarchy avoiding overlapping similar attributes. As part of the IIAD collection, we selecting mosque collection for this study to point out and to address three issues related to the usage of attributes from multiple metadata sets: (1) Similarity between attributes, (2) Specialization between attributes, and (3) Attributes categorization by subject.…”
Section: Usability Study and Discussionmentioning
confidence: 99%
“…They are used for effective classification and searching for digital resources in bibliographical, digital databases and visual archives. Categories help the users to navigate inside the digital data collections [1]. By grouping the data by comprehensible categories, the users can quickly eliminate what is not relevant or not interesting, and just look at the subject related to their interest.…”
Section: Multi-faceted Resource Categorizationmentioning
confidence: 99%
“…The Resource Categorisation Path is denoted RCP. Each node of the path (denoted α i ) is associated with a topic name and a list of descriptors (denoted δ), we defined RCP as (1) where δ i,j represents the j th descriptor of the ith node, n is the number of nodes and p the number of descriptors in the ith node.…”
Section: Topic-map Based Multi-faceted Metadata Supportmentioning
confidence: 99%